The Effect of Active Learning Model of Quiz Team Type on the Learning Outcomes of Students - Ilham Assidiq; Dian Firdiani; Elihami Elihami; Jamaluddin Ahmad; Yunus Busa (Edumaspul: Jurnal Pendidikan, 2022)
This study is a quasi-experimental study that aims to determine the existence of positive effects of active learning type quiz team of student learning outcomes with "The Only posttest Control Design". The population in this study were all students in class XI IPA. The samples was obtained by randomly. Class XI IPA 2 as a control class and class XI IPA 3 as a experiment class. The study consist of two variables, are the Active Learning Type Quiz Team as independent variables and learning outcomes as the dependent variable. The data obtained through test of learn result to the subject matter of colloidal systems were analyzed using descriptive statistics and inferential statistics. Descriptive analysis results showed the average value of the control class is 68 with a deviation standard of 12.44 while in the experimental class the average was 76.08 with a deviation standard is 11.12 with the thoroughness of 79.16% for the control class and 92% for experiments class. The results of hypothesis testing using t-test , ​​obtained tcomputation = 2.41 and ttable= 2.019 at significance level α = 0.05 with df = k-3, where tcomputation > ttable which means H0 rejected and H1 accepted. This showed that there are positive effect of active learning types quiz team of student learning outcomes.